Occurrences, distributions, and bioactive compounds of marine seaweeds in the southeast coasts of Bangladesh. - Chowdhury, Md Sabbir; Akter, Latifa; Kabir, Md Humayon; Islam, Junayetul; Nasrin, Morsheda; Ayman, Ummay; Kalam, Md Abul; Haque, Ziaul (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The study was conducted to assess the seasonal and geographical distributions, proximate compositions, and secondary metabolites of some of the commercially important seaweed species in the southeast coasts of Bangladesh. Materials and Methods: A temporal survey was conducted to know the seasonal and monthly distribution of seaweeds in different areas of the southeast coasts in Bangladesh. The representative samples were collected for proximate analysis and phytochemical screening by high-performance liquid chromatography. Results: The results showed that Saint Martin’s Island was the hotspot for the seaweeds in Bangladesh but sporadically distributed in the different areas of Cox’s Bazar district. Enteromorpha intestinalis and Hypnea musciformis were found from October to April, while the rest of the seaweed species were mostly observed during the winter season. The highest crude protein with the lowest crude fiber was found in Gracilaria tenuistipitata, but the highest ash content was recorded in E. intestinalis. However, the highest level of tannin and saponin was found in Asparagopsis taxiformis, whereas the lowest was in Sargassum flavicans. Conclusion: The occurrences and distributions of seaweeds vary depending on the species in the southeast coastal areas of Bangladesh, where Saint Martin’s Island is the largest reservoir. Most of the marine seaweeds found in the coastal areas of Bangladesh are rich in nutritive and bioactive compounds, which can be used as an alternative source of animal feed/feed additives for climate-smart livestock production. J. Adv. Vet. Anim. Res., 12(2): 549–557, June 2025 http://doi.org/10.5455/javar.2025.l919